MODEL KOMUNIKASI ANTARBUDAYA EKSPATRIAT GUANGDONG MACHINERY EXP.IMP.LTD CHINA (GMC) DENGAN ORANG INDONESIA DALAM RANGKA MENJALIN KERJASAMA DENGAN ORANG INDONESIA DI SURABAYA - Virgini Olaga Natalia, Imanuel (Scriptura, 2007)
Communication model produced by every communication performer was varied. The differences were naturally caused by frame of references and fields of experiences. And if we pulled it further backwards%2C actually differences of frame of references and fields of experiences were results of varied cultures of every person. Culture was a concept that resurrected interests. Formally%2C culture could be defined as a comprehensive pattern. (Mulyana and Rahmat%2C 2002%2C h. 26). Cultures appear in language patterns take form of activities and behaviors that function as models for actions of self-adjustment and communication style that enable people live in any particular society in any particular geographical environment at any particular technical development extent and at any particular time. Communication and inter-cultural relations are reciprocal and influenced by each other. What we discuss about%2C how we talk about it%2C what we care and neglect%2C what we think about and how we think about it affected by culture. Ultimately%2C what we talk about and how we talk about it%2C and what we see contribute to establish%2C determine and resurrect our cultures. Cultures will not survive without communication%2C nor will the other way around. Each of them can not change without causing changes of others. (Mulyana and Rakmat%2C 2002 h.37). Abstract in Bahasa Indonesia : culture%2C communication model